The role of Th17 cells in endocrine organs: Involvement of the gut, adipose tissue, liver and bone - Zi, Changyan; Wang, Die; Gao, Yongxiang; He, Lisha (Frontiers in Immunology, 2023)
T Helper 17 (Th17) cells are adaptive immune cells that play myriad roles in the body. Immune–endocrine interactions are vital in endocrine organs during pathological states. Th17 cells are known to take part in multiple autoimmune diseases over the years. Current evidence has moved from minimal to substantial that Th17 cells are closely related to endocrine organs. Diverse tissue Th17 cells have been discovered within endocrine organs, including gut, adipose tissue, liver and bone, and these cells are modulated by various secretions from endocrine organs. Th17 cells in these endocrine organs are key players in the process of an array of metabolic disorders and inflammatory conditions, including obesity, insulin resistance, nonalcoholic fatty liver disease (NAFLD), primary sclerosing cholangitis (PSC), osteoporosis and inflammatory bowel disease (IBD). We reviewed the pathogenetic or protective functions played by Th17 cells in various endocrine tissues and identified potential regulators for plasticity of it. Furthermore, we discussed the roles of Th17 cells in crosstalk of gut-organs axis.